EFFECT OF AEROBIC COMPOST APPLICATION ON THE GROWTH OF NATAR 1 (Piper nigrum L.) SEEDLINGS (Agrosys: Journal of Agronomy and Sustainable Crop Systems, 2026)
Limited availability of superior seedlings and appropriate growing media has contributed to the decline in pepper production in Indonesia. Improving nursery media quality through the application of aerobic compost is expected to enhance nutrient availability and promote optimal seedling growth. This study aimed to determine the best dose of aerobic compost in the growing medium to obtain the optimal growth of pepper (Piper nigrum L.) seedlings of the Natar 1 variety. The research was conducted in a greenhouse at the Faculty of Agriculture, University of Lampung, from May to September 2025. The experiment was arranged in a Randomized Block Design (RBD) with three soil-to-aerobic compost ratios, namely 1:0 (P1), 1:1 (P2), and 2:1 (P3) (v/v), each replicated nine times. Data were analyzed using analysis of variance followed by the Honestly Significant Difference (HSD) test at a 5% significance level. The results indicated that aerobic compost application significantly affected most growth variables. Treatments P2 and P3 resulted in better growth performance than P1, as shown by increased total branch length, total leaf number, total leaf area, leaf greenness, stem diameter, branch diameter, shoot fresh and dry weight, root volume, and root fresh and dry weight. However, the number of branches and leaves on the longest branch were not significantly influenced. In conclusion, soil-to-compost ratios of 1:1 and 2:1 effectively enhanced the growth of Natar 1 pepper seedlings four months after application.